Blestemul ariciului . The Curse of the Hedgehog - Budrala, Dumitru (The Visual Anthropology Foundation Sibiu, 2004)
The film follows the life of an extended Roma family for a whole year. They belong to the “Baesi” group of Roma and live in extreme poverty. The filmmaker accompanied them on the way from their dwelling place in the mountains to the lowland villages, where they try to trade handmade goods for food or money. These winter tours are survival trips for them, as they have no other income whatsoever. However, the film is more than the story of their struggle to survive. During the 100 minutes, it becomes clear why they refuse to work the land and how they relate to the Romanian shepherds, and to the rich Baesi from their village whom they call “businessmen,” who make large fortunes from selling fake rings abroad. Mythological thinking comes into play in their everyday life, along with their Christian Orthodox religiousness. This enables a better understanding of the absurdities and the pain that fill the lives of these people on the fringe of society. Through wit and humour, they survive, but also with a lot of cursing.